Field estimation of waterice phase composition of permafrost samples using a calorimetric method - Fortier, Richard; Allard, Michel; Sheriff, Fernando (Canadian Geotechnical Journal, 1996)
Waterice phase composition of undisturbed frozen ground samples obtained with a U.S. Army Cold Regions Research and Engineering Laboratory (CRREL) core barrel at different depths in permafrost mounds at Kangiqsualujjuaq and Umiujaq in northern Quebec was measured in the field using an adiabatic calorimetric method. Although the theoretical basis of adiabatic calorimetry is not fully established and the required correction factors are not available, the phase composition curves of the Kangiqsualujjuaq silty clay and Umiujaq fine sand are close to the ones determined by nuclear magnetic resonance and isothermal calorimetry for two soils with similar grain size distributions (Suffield silty clay and Manchester fine sand). A better understanding of thermal and physicomechanical aspects of frozen ground could be gained from the stratigraphic profile of waterice phase composition in permafrost mounds measured with the adiabatic calorimetric method. Key words: adiabatic calorimetry, unfrozen water content, permafrost, field tests.